The prognostic value of point-of-care blood glucose and lactate in canine and feline pyothorax: a retrospective analysis - Zhang, Lei; Grobman, Megan (Frontiers in Veterinary Science, 2025)
IntroductionBlood lactate and glucose are recognized as prognostic markers in various diseases in human and animals, yet studies evaluating their prognostic utility in canine and feline pyothorax are limited. This study aimed to investigate the prognostic utility of point-of-care (POC) lactate and glucose measurements, and identify clinical factors associated with survival in dogs and cats with pyothorax.MethodsA database search identified canine and feline pyothorax cases presenting to Auburn University between 2013 and 2023. Forty-three dogs and eight cats diagnosed with pyothorax were retrospectively enrolled. Baseline characteristics, clinicopathological data, and diagnostic findings were obtained from the medical records. POC blood glucose and lactate, recorded on admission and the following morning were documented, and lactate delta and clearance were calculated. Data on treatment was also collected. Additional outcome measures included survival and duration of hospitalization.ResultsIn dogs, non-survivors had significantly higher POC lactate concentrations on admission compared to survivors (3.4 mmol/L vs. 2.0 mmol/L, p = 0.023). Band neutrophil count was associated with in-hospital mortality at a univariable level (p = 0.03, OR 1.4). Stepwise Cox regression showed total solids and lactate concentration on admission as independent predictors of outcome. The area under the curve (AUC; 95% CI) for predicting in-hospital mortality based on lactate was 0.724 (0.568–0.879).ConclusionIn dogs with pyothorax, admission POC blood lactate concentration may serve as valuable prognostic tool to guide clinical management decisions, and an increased band neutrophil count is associated with poorer outcomes. Further large-scale studies are needed to confirm these findings.